Willingness, Knowledge, and Skills of Nurses in the Prevention and Management of Diabetic Foot Ulcers: A Cross-sectional Study in Indonesia - Suryani, Maria; Marwaningsih, Ririn; Winarni, Ida Nur Setia Budi; Hadjiman, Hadjiman; Andriyani, Erni Triyono (Chakra Brahmanda Lentera Institute, 2026)
Background: Nurses play a crucial role in the prevention and management of diabetic foot ulcers (DFUs); therefore, they should possess adequate knowledge, skills, and a willingness to do so. However, limited evidence exists on Indonesian nurses’ willingness, knowledge, and skills in the prevention and management of DFU. The study aimed to evaluate willingness, knowledge, and skills in the prevention and management of DFU among Indonesian nurses and to identify factors associated with these. Methods: A cross-sectional survey study was conducted. A total of 549 nurses working in medical-surgical inpatient units at four hospitals in Central Java, Indonesia, were selected using convenience sampling, given ease of online access and willingness to participate. Data on willingness, knowledge, and skill in the prevention and management of DFU were collected using an online survey. The Chi-square and logistic regression tests were used for data analysis. This study was reported in accordance with the STROBE guidelines. Results: The majority of nurses had no DFU training (65,2%), but had a bachelor's education level (51.9%) and were involved in DFU patient care (92.7%). Approximately 45.9% of nurses have adequate willingness, while 33.2% and 32.2% have adequate knowledge and skill, respectively. Higher education was associated with an adequate willingness (aOR 1.91, 95%CI:1.26-2.90, p=0.002), knowledge (aOR 1.55, 95%CI:1.07-2.26, p=0.020), and skills (aOR 1.72, 95%CI:1.18-2.51, p=0.005), among nurses. The DFU training was associated with adequate knowledge (aOR 2.71, 95%CI:1.86-3.95, p<0.001), and skills (aOR 2.63, 95%CI:1.81-3.85, p<0.001) of nurses. The DFU caring experience was also associated with nurses' knowledge (aOR 3.61, 95%CI:1.06-12.62, p=0.039) and skills (aOR 3.41, 95%CI:1.01-11.57, p=0.049). Furthermore, adequate knowledge (aOR 1.35, 95%CI:1.47-7.65, p=0.004) and adequate skills (aOR 5.60, 95%CI:2.41-13.01, p<0.001) were associated with willingness. Conclusion: Under half of nurses in hospital settings had adequate willingness, knowledge, and skill in the prevention and management of DFU. Higher education level, practical training, and caring experience were associated with the nurses’ willingness, knowledge, and skills. Adequate willingness was also associated with adequate knowledge and skill.